Evaluation Of The Targeting Accuracy Of The Smart Indonesia Program (PIP)(Case study of SD Negeri 52, SMP Negeri 6, and SMA Negeri 4Singaran Pati District, Bengkulu City): Evaluasi Ketepatan Sasaran Bantuan Program Indonesia Pintar (PIP)(Studi Kasus Pada Sd Negeri 52, Smp Negeri 6, Dan Sma Negeri 4 Kecamatan Singaran Pati, Kota Bengkulu) - Siska Octri Rahmadani; Henny Aprianty; Bobby Mandala Putra (Gayaku Publisher, 2026)
This study was driven by the inconsistency between official administrative data and the true economic conditions of Smart Indonesia Program (PIP) beneficiaries, resulting in improper targeting. This research seeks to assess the precision of targeting PIP beneficiaries and determine the factors contributing to this inaccuracy. The theoretical framework applied is William N. Dunn's theory of public policy evaluation, particularly focusing on the criteria of effectiveness, fairness, and precision, alongside Subarsono's notion of targeting precision. The approach used in this study is a qualitative method featuring a case study design. Techniques for data collection encompassed detailed interviews, observation, and record-keeping. The findings suggest that the execution of the Smart Indonesia Program (PIP) has proven successful in ensuring continuous academic engagement for students. Nonetheless, significant targeting precision has not been completely realized because of inclusion and exclusion mistakes. Internal factors consist of schools' limited ability to verify facts, whereas external factors are shaped by the unchanging quality of formal poverty data (Dapodik/DTKS), which does not reflect the reality of